On the Determination of Force Field Using Centrifugal Distortion Constants by Parametric Method: Application to Systems of 3 x 3 Order - Mohan, S.; Sundaraganesan, N. (Asian Journal of Chemistry, 2010)
The centrifugal distortion constants are used as additional parameters in fixing the unique force field of XYZ2 planar type (C2v), molecules which consists of a third order vibrational species A1 and a second order vibrational species B. It may be emphasised here that this method is applied for a problem of third order for the first time.